Reverse engineering from 3D mesh to ceramic product in the form of miranda kerr tea for one teapot in PT doulton Indonesia. Issue 1 (1st January 2021) - Anggoro, P.W.; Tan Wijaya, A.R.; Yuniarto, T.; Bayuseno, A.P.; Jamari, J.; Tauviqirrahman, M.; Setyohadi, D.B.
Abstract: The design and manufacturing strategy using reverse engineering (RE) for Miranda Kerr Tea for One Teapot are presented in this paper. A computer-aided reverse engineering system (CARE System) was applied to minimize file errors generated by scanning Miranda Kerr Tea for One Teapot sample products made from Bone China clay. Digital data from the scanning process is used to design a teapot model that is precise and accurate. The digital data generated by Next Engine 3D and the priXa 1588 CMM is then converted into stereolithography (STL) file format (triangle-based data). The process of making 3D CAD models consists of: editing the 3D mesh from the scanning results, 3D CAD design forming the size of the fire, the size of the model, and the 3D CAD milling process using PowerSHAPE with the final result in the form of the surface of each part of the Teapot product. Manufacturing optimization to get the optimal machining strategy used PowerMILL and CNC machines. The casting process becomes a follow-up process after machining the mold of the designed product. This research has succeeded in demonstrating the advantages of using CARE System technology in the national ceramic industry in Indonesia so that it can compete at national and international levels. This is based on the magnitude of the RE error value of less than 1.00 mm with a total processing time of 43 hours 18 minutes 10 seconds and a total cost of about $ 4172.35.